Determinants of Pentahelix Model in Developing the Halal Industry in Indonesia: Analytic Network Process (ANP) Approach - Maulana, Hartomi; Mohd Thas Thaker, Mohamed Asmy Bin; Zarkasyi, M. Ridlo; Taufani, Mochammad Kharits; Ramdani Harahap, Soritua Ahmad (Indonesian Journal of Halal Research, 2025)
The development of an industry cannot be realized without the role of stakeholders, and this also applies to the halal industry. This paper aims to examine the determinants of the pentahelix model in developing the halal industry in Indonesia. Qualitative approach by using the Analytic Network Process (ANP) used in this study. Ten respondents, including practitioners, academics, and policymakers, are selected to gather experts' opinions about developing the halal industry through the pentahelix model. The findings of this study show that business actors, who play a major role as producers and providers of halal products and are responsible for meeting halal standards, are the first priority determinant found in the pentahelix. An increase in understanding of halal knowledge, consistent discipline and professionalism, and having product development access of business actors will increase their role in developing the halal industry. The second priority determinant found is media, followed by government, academia, and community. The most prioritized sub-elements of the pentahelix aspect indicators, according to the respondents' agreement, are government support (government element) and knowledge and understanding of halal (business actor element). It indicates that government assistance is a priority due to its significant regulatory role in ensuring simple procedures and compliance with halal standards. In conclusion, the priority rank of determinant of pentahelix found is business actor (first rank), media (second rank), government (third rank), academia (fourth rank), and community (fifth rank). The study suggests that business actors play a crucial role in developing the halal industry, which may be enhanced in terms of their halal literacy and knowledge of halal products. The government's role in halal certification needs to be enhanced in order to ease the halal register for business actors.